Economic evaluation of third-line neratinib plus capecitabine versus lapatinib plus capecitabine with HER2+ metastatic breast cancer - Ren, Lanqi; Ren, Ning; Zheng, Yu; Yang, Yibei; Xu, Qiaoping (Frontiers in Oncology, 2023)
Background：Breast cancer (BC) is one of the most common malignant tumors in women. And human epidermal growth factor receptor 2-positive (HER2+) BC is overexpressed in 25% of BC patients, resulting in the predicament of poor prognosis. Though first-line and second-line treatment has been established, optimum third-line treatment is still mired in controversies for HER2+ metastatic BC (mBC). Therefore, this study analyzes the cost-effectiveness of neratinib plus capecitabine (N+C) and lapatinib plus capecitabine (L+C) over a 5-year time horizon from a payer perspective.Methods：A half-cycle corrected four-state Markov model was established to simulate the course of BC events and deaths in N+C and L+C armed patients. The data of this model were derived from NCT01808573 trail and other published literatures. One-way deterministic sensitivity analysis (DSA) was conducted to investigate the impact of variables and probabilistic sensitivity analysis (PSA) was performed based on second-order Monte Carlo simulation. Besides, subgroup analysis was performed to verify its cost-effectiveness in China.The base-case results found that N+C was in dominant position in 82.70% of the generation scenarios, providing an improvement of 0.